2011
DOI: 10.1016/j.hlc.2011.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Surgical Outcomes in Abdominal Solid Organ (Renal and Hepatic) Transplant Recipients: A Case Matched Study

Abstract: OBJECTIVES: This study aims to investigate the outcomes of cardiac surgery in patients with abdominal solid organ transplants and to compare them with the case-matched population undergoing cardiac surgery. METHODS:Data from all transplant recipients abdominal solid organ transplant (ASOT) N = 36 (30 renal and 6 hepatic) who underwent cardiac surgery in a single centre during the period from January 1997 to December 2010 were collected from hospital transplant registries and the cardiac database. The transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
1
13
1
Order By: Relevance
“…That may suggest that the STS mortality risk score is more accurate in predicting transplant patient mortality after heart surgery. Although others have reported no early mortality for liver transplant patients, we found no early mortality for the kidneypancreas transplant patients [26].…”
Section: Commentcontrasting
confidence: 78%
See 1 more Smart Citation
“…That may suggest that the STS mortality risk score is more accurate in predicting transplant patient mortality after heart surgery. Although others have reported no early mortality for liver transplant patients, we found no early mortality for the kidneypancreas transplant patients [26].…”
Section: Commentcontrasting
confidence: 78%
“…It is worth noting that our data demonstrate 15-year survival, whereas most studies show 1-to 5-year long-term survival [12,15]. Sharma and colleagues [26] found a 59% survival rate for transplanted patients 10 years after cardiac surgery. Their rate is still higher than the survival rate of our transplanted patients 10 years after cardiac surgery.…”
Section: Commentmentioning
confidence: 50%
“…Fourteen studies, involving 15,481 solid organ transplant recipients of whom 14,427 (95%) were kidney transplants, and 7,807,705 non-transplanted patients satisfied the inclusion criteria (Table 1: Summary of included studies). Non-emergent cardiac (5 studies) [5,18,20,24,27] and orthopaedic (5 studies) [16,17,19,22,23] surgery were the most commonly reported types of surgery. General surgical outcomes were reported in 3 studies [4,21,25].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…A single study assessed outcomes following urological/gynaecological procedures [26] and there were no studies in vascular surgery. Six studies assessed a single surgical procedure [16,17,19,22,23,26], while the remainder examined a combination of discipline-specific surgical interventions [4,5,18,20,21,24,25,27]. All but 4 studies [18,21,22,24] were from North America.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The number of KTR undergoing open heart surgery is steadily rising, as KTR live longer and have multiple risk factors for coronary heart and valve disease, including CKD, dialysis, posttransplant diabetes, arterial stiffness and immunosuppression (5). Even though surgical revascularization confers a high short-term risk, it is associated with favorable long-term outcome in the CKD population and probably also in KTR (6)(7)(8)(9)(10)(11). Since the first report on coronary artery bypass grafting in KTR in 1974 (12), numerous studies have been published (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%